2005
DOI: 10.1029/2005je002420
|View full text |Cite
|
Sign up to set email alerts
|

Major episodes of the hydrologic history in the region of Hesperia Planum, Mars

Abstract: [1] The High Resolution Stereo Color camera (HRSC) data over Hesperia Planum and its surroundings reveal important details of geologic episodes and water-related processes in this region. (1) The Noachian fluvial events of Hesperia Planum depression included accumulation of water and formation of a water/ice reservoir there. Later, the reservoir was depleted in several phases reflecting diminishing amounts of water. Climate changes and/or volcanism were important in these volatile releases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Greeley and Schneid (1991) were able to determine volume estimates for lavas during each epoch of Mars (Table 5), with the total martian history, excluding the unconstrained Early Noachian, accumulating $68.8 Â 10 6 km 3 . This same technique was also used by Ivanov et al (2005) to estimate the volume of lavas in Hesperia Planum, where craters where found to be buried by several hundred meters, with an estimated total volume for the unit of $0.4-0.7 Â 10 6 km 3 . Craddock and Greeley (2009) and Gillmann et al (2011) state that techniques have not changed sufficiently to update estimates of volumes of extrusives, as the Greeley and Schneid estimates have been the basis for models approximating outgassing as it pertains to past martian atmospheres.…”
Section: Volume Estimates and Atmospheric Implicationsmentioning
confidence: 99%
“…Greeley and Schneid (1991) were able to determine volume estimates for lavas during each epoch of Mars (Table 5), with the total martian history, excluding the unconstrained Early Noachian, accumulating $68.8 Â 10 6 km 3 . This same technique was also used by Ivanov et al (2005) to estimate the volume of lavas in Hesperia Planum, where craters where found to be buried by several hundred meters, with an estimated total volume for the unit of $0.4-0.7 Â 10 6 km 3 . Craddock and Greeley (2009) and Gillmann et al (2011) state that techniques have not changed sufficiently to update estimates of volumes of extrusives, as the Greeley and Schneid estimates have been the basis for models approximating outgassing as it pertains to past martian atmospheres.…”
Section: Volume Estimates and Atmospheric Implicationsmentioning
confidence: 99%
“…Unit A encompasses a broad range of terrain types and expected subsurface layering. For example, Hesperia Planum and Syrtis Major are dominated by lava flows with estimated thicknesses of up to 500 m (Ivanov et al, 2005) and 1 km (Hiesinger, 2004;Rogers et al, 2007), respectively. Hence craters smaller than $10 km may be sourcing their ejecta from entirely within these flows and the superposed aeolian fine-grained deposits (Putzig and Mellon, 2007).…”
Section: Some Examplesmentioning
confidence: 99%
“…De Hon, 1974, 1979, flood lavas on Mars (e.g. Ivanov et al, 2005) and dust mantles on Mars (e.g. Bleacher et al, 2003).…”
Section: Mantle Thicknessmentioning
confidence: 99%